Governance and the pluralisation of the state: implications for democratic citizenship - Chandhoke, Neera (2003)
The state has been pluralised and now shares power with sub-national governments, proliferating forms of network and partnership organisations, a variety of quasi-public and private organisations, NGOs and international agencies and other forms of supranational governance. what remains of the significance or meaning of the liberal democratic notion of the state as the undisputed centre of political aspirations and its task of pursuing the collective interest when it has been itself enmeshed in a number of organisations? How do we democratise bodies that are out of the reach of representation? How do we ensure that democratic procedures take into account background `inequalities? Governance in other words has thrown up major challenges for the liberal democratic project and we need to think this through. Or should we raise new questions for the project of governance itself? - Reproduced.
Keywords: Public administration